2011
DOI: 10.1103/physrevlett.106.246405
|View full text |Cite
|
Sign up to set email alerts
|

Nernst Response of the Landau Tubes in Graphite across the Quantum Limit

Abstract: We report on a study of the Nernst effect in graphite extended up to 45 T. The Nernst response sharply peaks when a Landau tube is squeezed inside the thermally fuzzy Fermi surface and presents a temperature-independent fixed point when the tube flattens to a single ring. Beyond the quantum limit, the onset of the field-induced phase transition leads to a drastic drop in the Nernst response signaling the sudden vanishing of Landau tubes. The magnitude of this drop suggests the destruction of multiple Landau tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In both systems, a field of 10 T suffices to attain the quantum limit. During the last few years, unexpectedly large oscillations of the Nernst response was reported in both bismuth [84] and graphite [21,85] in the vicinity of the quantum limit. In both these systems, when a few Landau tubes remain, a large oscillatory Nernst response dominates the monotonous background.…”
Section: Review Of Experiments Iv: Quantum Oscillations In Strong Magmentioning
confidence: 99%
“…In both systems, a field of 10 T suffices to attain the quantum limit. During the last few years, unexpectedly large oscillations of the Nernst response was reported in both bismuth [84] and graphite [21,85] in the vicinity of the quantum limit. In both these systems, when a few Landau tubes remain, a large oscillatory Nernst response dominates the monotonous background.…”
Section: Review Of Experiments Iv: Quantum Oscillations In Strong Magmentioning
confidence: 99%
“…In the early eighties, a phase transition in this system was discovered by Tanuma and co-workers who reported a sharp increase in the in-plane magnetoresistance of graphite at B≈25 T [8]. Numerous experimental studies followed [9][10][11][12][13][14][15] and confirmed the existence of a field-induced many-body state beyond a temperature-dependent critical magnetic field. Soon after the initial experimental discovery, Yoshioka and Fukuyama (YF) [16] ascribed this instability to a charge-density-wave (CDW).…”
mentioning
confidence: 99%
“…The present result helps to understand the evolution of the observed anomalies in the Nernst effect [12,29] (a measure of the entropy per carrier [30]) and the ultrasound measurements [13] caused by the transition. At low temperature, one expects that ordering induces a smooth variation in entropy (see [17]) and therefore a rounded drop in the Nernst response [12,29]. As the temperature increases the mean field component of the transition strengthens and the Nernst anomaly becomes a clear kink.…”
mentioning
confidence: 68%
“…In the early 80s Tanuma and co-workers [5] discovered the onset of an electronic phase transition at B=25T and T=1.3K. Since then, extensive electrical [6][7][8][9][10][11], thermo-electrical [12] and ultrasound measurements [13] at high magnetic field have established that graphite hosts a succession of, at least, two field induced phases [7,11] arising from electron-hole instabilities. Depending on the nesting vector considered and the strength of the electron-electron interaction, various types of charge [10,14], spin [15] density waves or an excitonic insulating phase [8,9,11,16] have been proposed.…”
mentioning
confidence: 99%